Persepsi Guru terhadap Pembelajaran Daring pada Masa Pandemi Covid-19 di MI Se-Kecamatan Rajagaluh Majalengka - Nafisah, Farhah Dzikrotun; Carlian, Yayan; Pratiwi, Inne Marthyane (Program Studi PGMI STAI Auliaurrasyidin Tembilahan, 2022)
This research is motivated by the existence of obstacles that occur in the online learning process. Obstacles that occur can lead to not achieving the competencies that must be possessed by students. The purpose of this study is to describe the teacher's perception of online learning, the implementation of online learning, the obstacles to online learning, and the inhibiting factors of online learning. This study uses a qualitative approach with a descriptive method. Data collection techniques used are observation, interviews, and documentation. Meanwhile, the data analysis techniques used are data reduction, data presentation, and drawing conclusions based on Miles and Huberman. The results show that teachers think online learning is the right strategy to use during the Covid-19 pandemic. The implementation is only in the form of assignments via whatsapp groups. The obstacles include decreased student enthusiasm for learning, students' difficulties in understanding learning material, and the lack of maximum learning provided. The inhibiting factor for online learning is in the learning device such as cellphone.